2012
DOI: 10.1155/2012/527238
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Drugs Use among Preoperative Patients: A Cross-Sectional Study in Italy

Abstract: Complementary and alternative drugs (CADs) are widely used in preoperative patients and may lead to potential interactions and adverse reactions. The aim of our study is to evaluate the prevalence and the predictors of CADs use among preoperative patients using data from an Italian survey. This cross-sectional study, which enrolled 478 patients (response rate: 83.5%), was carried out in three Tuscany hospitals (Italy). The prevalence of CADs use was 49.8%: 233 out of 238 participants used herbal products and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
(56 reference statements)
0
13
1
3
Order By: Relevance
“…Several survey studies have pointed out the outcome that herbal medicines are usually used particularly by women with higher education (20)(21)(22), whereas some studies revealed no correlation between the educational status and HMP use (23,24). Nevertheless, we have not obtained a clear finding from our own study.…”
Section: Discussioncontrasting
confidence: 67%
“…Several survey studies have pointed out the outcome that herbal medicines are usually used particularly by women with higher education (20)(21)(22), whereas some studies revealed no correlation between the educational status and HMP use (23,24). Nevertheless, we have not obtained a clear finding from our own study.…”
Section: Discussioncontrasting
confidence: 67%
“…Factors that may have influenced the level of use include social influences, economic status, age, religion, gender, accessibility to health care, ethnicity and availability of alternate health care. 15 A. sativum was used by 22.9% of patients in the UK study, but total use was low. Hospital 3 also covers a larger geographical area and includes a more rural community, so ease of access to health care and cost may have been a factor contributing to the higher prevalence of herbal medicine use.…”
Section: Discussionmentioning
confidence: 84%
“…13,15 In terms of the types of herbs used, we reported a high level of use (74%) of A. sativum. Factors that may have influenced the level of use include social influences, economic status, age, religion, gender, accessibility to health care, ethnicity and availability of alternate health care.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A komp lementer terápiás gyógymódokkal kapcsolatos pozitív attitűd betegek és orvosok között is jellemzően kapcsol ható a fiatal és középkorú, magasan képzett hölgyekhez [25][26][27][28]. Svédországban az egészségügyi dolgozók 55,8%a tanulna szívesen CAMt [29].…”
Section: Tanulási Kedv éS Klinikai Alkalmazásunclassified